# How do you solve #2 ln x+ ln x^2=3#?

##### 1 Answer

Dec 4, 2015

#### Explanation:

First of all, you need to "unite" the

This can be done with the logarithmic rules:

#log_a (n) + log_a (m) = log_a (n * m )#

#r * log_a(n) = log_a(n^r)#

So, you can transform your equation as follows:

#color(white)(xx)2 ln x + ln x^2 = 3#

#<=> 2 ln x + 2 ln x = 3#

#<=> 4 ln x = 3#

... divide both sides by

#<=> ln x = 3/4#

Now, the inverse function for

This means that you can apply

#<=> e^ln(x) = e^(3/4)#

#<=> x = e^(3/4)#